A SOLDIER-POET TESTIMONIES: THE US-IRAQI WAR IN BRIAN TURNER'S POETICS - Mihsin, Haider (International Journal of Language and Literary Studies, 2025)
This paper sheds light on Brian Turner's poems "At Lowe’s Home Improvement Center" and "Caravan" as testimonies of an American soldier-poet, Brian Turner (1957-), who held the position of an infantry unit leader during the 2003 US-led invasion on Iraq under the pretext of the existence of mass destruction weapons. It argues how Turner, as an eyewitness to the fatal violence of war against Iraq, exposes the traumatic memories of a survivor who experienced these events in person. This study shows how the concept of testimony is employed in Brian Turner's poems, "At Lowe’s Home Improvement Center" and "Caravan," as a form of a poetic model of literature and statement of evidence presented to the history of humanity. The findings of this study demonstrate Turner's sufferings as a veteran who served in the US-led war against Iraq. Turner's selected poems, as testimonial documents, show how those who have lived through war endure the effects of war. He, as a survivor of political violence, attests to the facts of history and prevents removing the events through negation, denial, or forgetting. To conclude, the literature of war poetry bears witness to the aftermaths of violence. Since 2003, the US-Iraqi War has increasingly influenced writings that recounts the experiences of wartime. Turner's testimonial poems explore how writing poetry acts as a means of recovery from trauma and as a method of bearing witness and giving testimonies of the devastation and negative effects resulting from the recent Iraq war.